2016
DOI: 10.1080/02770903.2016.1218011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of air purifier on health outcomes and indoor particles in homes of children with allergic diseases in Fresno, California: A pilot study

Abstract: Intervention with air purifiers reduces indoor PM levels with significant improvements in nasal symptoms in children with allergic rhinitis in Fresno.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 19 publications
4
54
0
Order By: Relevance
“…According to the available studies, nasal application of mometasone or oral application of montelukast reduces the intensity of mild obstructive sleep apnea in children [65,66]. Another way of alleviating the symptoms of nasal obstruction may be the use of household air filters [67]. However, so far, no studies analyzing the direct impact of air filters on obstructive sleep apnea have been conducted.…”
Section: Allergic Diseases Environmental Pollution and Osamentioning
confidence: 99%
“…According to the available studies, nasal application of mometasone or oral application of montelukast reduces the intensity of mild obstructive sleep apnea in children [65,66]. Another way of alleviating the symptoms of nasal obstruction may be the use of household air filters [67]. However, so far, no studies analyzing the direct impact of air filters on obstructive sleep apnea have been conducted.…”
Section: Allergic Diseases Environmental Pollution and Osamentioning
confidence: 99%
“…Of the seven eligible studies, six were randomized controlled trials (14,15,(23)(24)(25)(26) and one was a randomized cross-over study (27). The study population included asthmatics (14,15,(23)(24)(25)(26) and patients with COPD (27); the study about interstitial lung disease or bronchiectasis was not identified.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Six of the identified studies were conducted in North America (14,15,(23)(24)(25)(26); the remaining study was conducted in Beijing, China (27).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations